PENGARUH BRAND AWARENESS DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN - Widianti, Ayun; Mulyati, Diana Juni; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2018)
Â This study aims to analyze how much influence brand awareness and product quality to customer loyalty. Sampling method used is Accidental Sampling Method. The sample in this research is 100 customers who buy Bodypack products in Surabaya area and then analyzed the data obtained by using quantitative data analysis.Quantitative analysis includes: validity and reliability test, multiple linear regression analysis, hypothesis testing through t test and F test, and coefficient of determination analysis (R2).The data that has met the validity and reliability test are processed so as to produce the following regression equation: Y = 0,608 + 0.376X1 + 0,448X2Where is the variable of Customer Loyalty (Y), Brand Awareness (X1) variable and Product Quality variable (X2).Hypothesis testing using t test showed that both independent variables studied proved to significantly influence partially to dependent variable Customer Loyalty.Then through the F test can be seen that the two independent variables studied simultaneously affect the dependent variable Customer Loyalty.Adjusted R Square number of 0.707 indicates that 70.7 percent of Customer Loyalty variables can be explained by the two independent variables in the regression equation.While the remaining 29.3 percent is explained by other variables outside the two variables used in this study.Â Keywords: Brand Awareness, Product Quality and Customer Loyalty